Task matters: A structural-instrumental analysis of the autonomy of Hong Kong government bodies - Painter, Martin; Yee, Wai-Hang (2011)
What might account for the varying degrees of autonomy granted to public agencies? One broad range of answers is provided by a structural-instrumental perspective on organizations, which assumes that the assignment of autonomy is a response to structural features of organizing on the one hand and to task considerations on the other. Taking the case of Hong Kong, data from a survey of chief executives of 111 government agencies on perceptions of autonomy are analyzed to explore a series of propositions concerning the relationship between structure, task, and perceived autonomy. The method of ordinary least square regression is used to analyze the data. Overall, the findings show that variables describing key features of structure and task do help to explain degrees of autonomy. However, two propositions drawn from rational choice theory concerning task-related variables are not confirmed: public service delivery organizations are under tighter, not looser control, whereas regulatory agencies show no tendency toward autonomy. Interpretation of the findings points to significant features of Hong Kong's constitutional and political history which highlight the importance of contextualization. - Reproduced.
Keywords: Government organizations